Groundwater nutrient concentrations in residential areas with different wastewater treatments: a long-term monitoring study to inform adaptive management strategies - Souto, Leesa; Listopad, Claudia; Barker, Virginia; Gubler, Anthony; Appelt, Juliane (Frontiers in Marine Science, 2025)
Groundwater nutrient pollution is problematic as it bypasses upland and wetland filtering mechanisms, seeping biologically available forms of nitrogen and phosphorus directly into receiving surface waters and fueling primary production. There are few cases where coastal managers are adopting a groundwater adaptive management approach to address this hidden and potentially significant source of nutrient pollution. Water and habitat deterioration in the Indian River Lagoon (IRL) coastal estuary has become a serious concern of scientists, resource managers, and the community. Brevard County, FL implemented an Adaptive Management approach that relied on research to prioritize nutrient sources and evaluate projects for funding through the voter approved Save our Indian River Lagoon project plan. The research found significant differences in groundwater nutrient concentrations between communities with different wastewater treatments: 1) septic systems, 2) municipal sewer, and 3) municipal sewer with reclaimed wastewater for irrigation. Wastewater retrofit projects were implemented to reduce groundwater nutrient loads and pre-post retrofit groundwater nutrient concentrations were compared to evaluate the success of meeting objectives. More post-retrofit monitoring is needed to model the associated pollutant load reductions, which is the next phase of the adaptive management approach. Research results were shared with stakeholders to provide foundational knowledge, inform management strategies and policy changes, and demonstrate progress toward meeting prescribed load reductions. The deliberate and iterative nature of the County’s use of monitoring to establish baselines and guide resource management decisions is an example of a large-scale groundwater adaptive management (AM) approach to estuarine restoration.